2006
DOI: 10.1210/jc.2005-2009
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Cancers in Thyroid Cancer Patients: A Multinational Record Linkage Study

Abstract: Pooled data from 13 cancer registries show a 30% increased risk of second primary cancer after thyroid cancer and increased risks of thyroid cancer after various primary cancers. Although bias (detection, surveillance, misclassification) and chance may contribute to some of these observations, it seems likely that shared risk factors and treatment effects are implicated in many. When following up patients who have been treated for primary thyroid cancer, clinicians should maintain a high index of suspicion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(158 citation statements)
references
References 28 publications
12
133
1
4
Order By: Relevance
“…Recently, Sandeep et al published a large multinational record linkage study on second primary cancers in thyroid cancer patients (21). The study was conducted at 13 population-based cancer registries in Europe, Canada, Australia, and Singapore and included a cohort of 39.002 patients with primary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sandeep et al published a large multinational record linkage study on second primary cancers in thyroid cancer patients (21). The study was conducted at 13 population-based cancer registries in Europe, Canada, Australia, and Singapore and included a cohort of 39.002 patients with primary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic metastasis from papillary thyroid cancer occurs to neck lateral nodal groups of levels II, III, IV and central (level VI) lymph nodes. Thyroid cancer patients have an increased risk of developing a second cancer as either synchronous or metachronous [4]. In a pooled analysis of primary carcinoma thyroid patients from 13 registries, Sandeep et al [4] found a 30% increase in risk of second cancers including salivary gland, kidney, prostate, skin, breast, brain, myeloma, leukemia, and non-Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer patients have an increased risk of developing a second cancer as either synchronous or metachronous [4]. In a pooled analysis of primary carcinoma thyroid patients from 13 registries, Sandeep et al [4] found a 30% increase in risk of second cancers including salivary gland, kidney, prostate, skin, breast, brain, myeloma, leukemia, and non-Hodgkin lymphoma. On another side primary head neck cancer patients also have increased incidence (2-3% per year) of development of second primary cancer [5].…”
Section: Discussionmentioning
confidence: 99%